The head & neck II, Temporal bone & posterior cranial fossa - Hillen, Berend (Amsterdam : Elservier Science, 1994)
(Producer) Presents 9,000 images of normal anatomy and 1,200 correlative images from CT, MRI, and histology, and enables medical professionals to explore interactively the major structures of the temporomandibular joint, tympanic cavity, labyrinth, facial canal, parapharyngeal space, and skull base (from sella turcica to foramen magnum).
CD is available at Koleksi Media, Perpustakaan HUKM
Includes one CD-I disc and one CD-ROM
System requirements: CD-I disc: CD-I player upgraded with a Digital Video (DV) cartridge; television.
System requirements: CD-ROM disc: IBM-compatible PC, 386-33 CPU or better; 4 Mb internal memory, 3.5 Mb free disc space; Microsoft Windows 3.1; CD-ROM player (double-speed recommended); accelerated video card; mouse.
Keywords: Temporal Bone -- anatomy & histology -- CD-ROM; Cranial Fossa, Posterior -- anatomy & histology -- CD-ROM; Diagnostic Imaging -- CD-ROM